PROFIL KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI IKATAN KIMIA - Fitriah Khoirunnisa; Ardi Widhia Sabekti (Jurnal Pendidikan Kimia Indonesia, 2020)
The purpose of this study is to analyze students' critical thinking skills in the Chemistry Bond subject. This research is quantitative research with a descriptive approach. The participant of this research were 190 grade X and XI students from several high schools in Tanjungpinang city. The sampling technique was done by purposive sampling at several schools accredited A and B by BSNP. Data collection techniques used 8 test instruments representing 4 aspects of critical thinking, including aspects of providing explanations, building basic skills, managing strategies-tactics, and concluding. Classically, the critical thinking ability of high school students Tanjungpinang city on the Chemical Bond subject is still relatively low with average score is 34.45.